Obvladovanje mesta - Dimitrovska Andrews, Kaliopa (Urbani izziv, 1998)
The paper briefly discusses features of the current town planning systems in Europe and in Slovenia, and on-going changes relating to new approaches to town planning, focussing on specific aspects, namely: on the need for an urban design strategy and informal planning documentation support, on planning gain and on action planning. Three examples of design issues are discussed: implementation of statutory plans (The Highbury initiatives, Birmingham), negotiated urban form (Broadgate centre, London) and development control (Rog renewal, Ljubljana). Special attention is given to public involvement in design issues.
Keywords: mesta; prostorsko planiranje; spatial planning; urbanism; urbanistično planiranje; urbanizem